Motor pattern of free-style swimming - Vaday, M.; Nemessuri, M. (First International Symposium on "Biomechanics and Swimming, Waterpolo and Diving", 14-16 September 1970. Proceedings, 1971)
The free-style swimming is the most effective methode of swimming. because this movement is the quickest locomotion in the water (3). Its movement form stands also near to the instinctive way of swimming (2). The mentioned two reasons were the fundamental causes for studying the freestyle motor pattern. Our aim was to determine by means of objective measurewents those main active forces that give the propulsive force of free-style swimming, and to define on that basis the motor direction pattern.